Atitudes do design estratégico em organizações com perfil inovador - Paz, Cesar Fernando da Silva (Universidade do Vale do Rio dos Sinos, 2018)
This study aims to identify evidence of strategic design attitudes in organizations that survive and grow as a basic unit of the new information economy and within the new morphologies of contemporary society. Along this research work, these organizations are extensively called organizations with an innovative profile. The purpose of the investigation is to observe the attitudes of strategic design in these spaces to reflect on who the strategic designer currently is today, and what characterizes such articulator as someone able to design strategies for these organizations. The research is based on the attitude design model approach by Michlewski (2008, 2015), confronted by the view of experts in strategic design, to deepen such perspectives in a theoretical and possible dialogue between design attitude and strategic design. From the elements built in such dialogue, the expanded design attitude model for strategic design is born. The expanded model is generated from generic design attitudes and specific attitudes of strategic design. To conclude with, the research presents a case study, in which the expanded design attitude model is adopted in order to analyze the attitudes of strategic design in a Brazilian company with a technological base and innovative profile.
Keywords: Design Attitude; Design Estratégico; Inovação Organizacional; Design Attitude; Strategic Design; Organizational Innovation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial